A National Crisis or Localized Problems? Getting Perspective on the Scope and Scale of the Teacher Shortage - Patrick Murphy; Michael DeArmond; Kacey Guin (Arizona State University, 2003)
Despite the considerable attention the popular press has devoted to the question of teacher shortages, there have been surprisingly few attempts to systematically measure the size and nature of the problem. This article attempts to estimate the size and nature of the celebrated teacher shortage of the late 1990s by using data from the U.S. Department of Education's 1999-00 School and Staffing Survey. While limitations of the SASS data do not allow us to directly estimate the absolute size of the shortage, they do allow us investigate its relative impact. An examination of the data shows that the problem was distributed unevenly: urban schools and those with relatively high populations of minority and low-income students bore the brunt of the shortage; southern and western states had more problems filling teaching slots than other regions did. These findings suggest that state and local officials should keep distributional concerns in mind when they design policies to improve teacher recruitment and retention.